Otunba Mohammed Aliu Jobi-Fele : his life, his adventures - Oguntuase, Tunji (Lagos, Nigeria : Joe Tularu and Associates, 2002)
An authorized biography of Otunba Mohammed Aliu Jobi-Fele's first six decades in life. A narrated account of his commitment to industry, hard work and integrity in public service.
Includes index.
oif 15/04/15
Loan
Keywords: Jobi-Fele, Otunba Mohammed Aliu, -- 1940-; Chief executive officers -- Nigeria -- Biography. .; Industrialists -- Nigeria -- Biography